Phenotype of NK Cells Determined on the Basis of Selected Immunological Parameters in Children Treated due to Acute Lymphoblastic Leukemia. Issue 52 (December 2015) - Koltan, Sylwia; Debski, Robert; Koltan, Andrzej; Grzesk, Elzbieta; Tejza, Barbara; Eljaszewicz, Andrzej; Gackowska, Lidia; Kubicka, Malgorzata; Kolodziej, Beata; Kurylo-Rafinska, Beata; Kubiszewska, Izabela; Wiese, Malgorzata; et al.
Abstract : Abstract: Acute lymphoblastic leukemia (ALL) is the most frequent pediatric malignancy. The chemotherapy for ALL is associated with a profound secondary immune deficiency. We evaluated the number and phenotype of natural killer (NK) cells at diagnosis, after the intensive chemotherapy and following the completion of the entire treatment for patients with ALL. The fraction, absolute number, and percentage of NK cells expressing interferon-γ were determined in full blood samples. The fraction of NK cells expressing CD158a, CD158b, perforin, A, B, and K granzymes was examined in isolated NK cells. We have shown that patients assessed at ALL diagnosis showed significantly lower values of the fraction of NK cells and percentage of NK cells with the granzyme A expression. Additionally, the absolute number of NK cells, the expression of CD158a, CD158b, perforin, and granzyme A were significantly lower in patients who completed intensive chemotherapy. Also, there was a significantly higher fraction of NK cells expressing granzyme K in patients who completed the therapy. Abnormalities of NK cells were found at all stages of the treatment; however, the most pronounced changes were found at the end of intensive chemotherapy.